Different aspects of opioid use in rheumatoid arthritis patients - Dorota Sokół; Adrian Undziakiewicz; Iga Dudek; Jakub Czarnota; Małgorzata Drozd; Michał Dobrzyński; Tomasz Skubel; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Background: Rheumatoid arthritis (RA), chronic severe non-cancer pain and the use of prescription opioids are now an increasing and common problem. Both RA and its comorbid pain have different mechanisms and their control can prove challenging, especially when patients are unresponsive to non-opioid analgesics or have side effects. The aim of the study is to analyze the available results of research and meta-analyzes on the use of opioids among patients with rheumatoid arthritis. Materials and methods: the literature available on the PubMed platform and published between 2010 and 2020 was analyzed. Results and conclusions: The use of opioids can cause a number of side effects, including misuse, abuse or addiction to these drugs. These phenomena are becoming more common in European and North American populations, as well as more and more people are using opioids in long-term therapy, despite the lack of evidence of a positive effect of such treatment in people with RA. In RA patients, frequent combinations of opioids with other drugs, for example benzodiazepines or anti-anxiety agents, are also observed, as well as side effects specific for this group of patients, such as osteoporotic fractures.